2017
DOI: 10.5539/ies.v10n10p39
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Carousel Feedback and Round Table Cooperative Learning Models to Improve Student’s Higher Order Thinking Skills (HOTS) and Social Studies Learning Outcomes

Abstract: This Classroom Action Research aims to improve students' HOTS (High Order Thinking Skills) and Social Studies learning outcomes through the application of Carousel Feedback and Round Table cooperative learning methods. This study was based on a model proposed by Elliott and was implemented for three cycles. The subjects were 30 female students of the eight graders of Junior High School Islam Terpadu Darul Azhar, South East Aceh, Aceh, Indonesia. The data collection instruments include observation, test, interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
1
10
0
2
Order By: Relevance
“…Moreover, Kagan [17] also assumes that this technique can be functioned to enhance the students' social and thinking skills. It is in line with the study from Yusmanto, et al [18] that found carousel feedback and roundtable cooperative learning models could increase students' HOTS and Social Studies learning outcomes. Carousel feedback provides an opportunity for students to work in groups to discuss and understand issues, problems, and concepts to remember facts, beliefs, information, and/or agreements.…”
Section: Introductionsupporting
confidence: 90%
“…Moreover, Kagan [17] also assumes that this technique can be functioned to enhance the students' social and thinking skills. It is in line with the study from Yusmanto, et al [18] that found carousel feedback and roundtable cooperative learning models could increase students' HOTS and Social Studies learning outcomes. Carousel feedback provides an opportunity for students to work in groups to discuss and understand issues, problems, and concepts to remember facts, beliefs, information, and/or agreements.…”
Section: Introductionsupporting
confidence: 90%
“…Sehingga dengan diterapkannya model tersebut maka diharapkan rasa kepercayaan diri siswa meningkat dan akan berpengaruh kepada peningkatan hasil belajar siswa. Pemilihan model Carousel Feedback ini dilakukan dengan memperhatikan teori dasar mengenai model Carousel Feedback yang telah dipaparkan sebelumnya serta berdasarkan hasil maupun temuan penelitian terdahulu yakni penelitian yang telah dilakukan oleh (Yusmanto, et al, 2017) di mana hasil penelitiannya menunjukkan bahwa model Carousel Feedback terbukti mampu meningkatkan kemampuan siswa. Selain itu penelitian dari (Martha, 2015) juga menunjukkan adanya peningkatan hasil belajar siswa setelah mengikuti pembelajaran dengan model Carousel Feedback and Showdown.…”
Section: Abstrakunclassified
“…Hasil ini menunjukkan bahwa self efficacy diri siswa juga mengalami peningkatan setelah dilakukan pembelajaran dengan Carousel Feedback and Showdown. Hasil penelitian ini sejalan dengan hasil penelitian dari (Yusmanto, et al, 2017) dan (Martha, 2015) serta mendukung pendapat dari (Kagan & Kagan, 2009) yakni model Carousel Feedback and Showdown mendorong siswa untuk aktif belajar sehingga meningkatkan pemahaman siswa dan berdampak pada meningkatnya hasil belajar.…”
Section: Pembahasanunclassified
“…The ability to think that is still low does not match the needs of modern society, that is one of them requires the ability to think at a higher level [7]. Whereas 21st Century Learning places greater emphasis on students' ability to do Higher Level Thinking Skills (HOTS) [8].…”
mentioning
confidence: 99%
“…Paying close attention to these problems To improve higher order thinking skills (HOTS) is not only centered on students, but also influenced by teacher strategies [12]. So students can succeed in the ability to think at a high level (HOTS) in science learning, it requires process skills, it must be brave to change the learning paradigm from teacher-centered learning to student-centered.…”
mentioning
confidence: 99%